AB1037 Relationship between calcium pyrophosphate dihydrate crystal and operated knee osteoarthritis -gender specific analyses-. (12th June 2018) - Nishikawa, M.; Takami, K.; Owaki, H.; Fuji, T.
Abstract : Background: Calcium pyrophosphate dihydrate (CPPD) crystal deposition disease is a common arthritic disorder in mainly elderly patients. CPPD crystals are found in multiple joints in association with severe cartilage degeneration in osteoarthritis (OA). The knee is a key target site for both CPPD crystals and OA. CPPD crystals are also one of the common types of crystals causing crystal-induced inflammatory arthritis. There is a need to elucidate factors that can cause progression of knee OA. To address this question, we investigated the relationship between CPPD crystals and operated knee OA. Objectives: We investigated the relationship between CPPD crystal and operated knee OA separated by gender. Methods: Three hundred sixty-six unicompartmental knee arthroplasty (UKA), total knee arthroplasty (TKA) and high tibial osteotomy (HTO) (average age 73.3: male 59: female 307) were performed for over grade III knee OA classified by Kellgren-Lawrence grading scale from 2010 to 2017. At the operation, joint fluids were collected and elucidated the CPPD crystal using polarising microscope. We evaluated the relationship between CPPD crystals, and age, body mass index (BMI), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), matrix metalloproteinase-3 (MMP-3) at the operation. We defined the osteophyte formation degree (OFD) as grade 0–3 1 . We also defined the lower extremity alignment as varus (femorotibial angle: FTA ≥180°), neutral (170°≤FTA<180°) and valgus (FTA <170°). The relationship between CPPD crystals, and osteophyte formation and lower extremity were also evaluated. Results: CPPD crystals were detected from 101 Knee OA (27.6%). CPPD(+) rate in female (30.0%: 92/307) was significantly higher than that in male (15.3%: 9/59). There was a significant difference between CPPD(+) and (-) in male about only FTA (186.9°/182.0°). There were significant differences between CPPD(+) and (-) in female about age (76.3/72.4), FTA (182.7°/183.2°), BMI (24.9/26.6). The more severe OFD became, the higher CPPD(+) rate was in female, significantly. CPPD(+) rate in valgus knees (60.9%) was higher than that in varus knees (29.6%) in female significantly. Conclusions: The European League Against Rheumatism (EULAR) reported that female gender was not a risk factor associated with CPPD crystals 2 . In contrast, a recent study using a relatively large sample size of Japanese cadaveric knees showed a significant correlation for CPPD crystals and female gender 3 . Our data also showed a significantly high CPPD(+) rate in females. Because our data were based on Japanese patients only, Japanese ethnicity may influence the gender difference in the CPPD(+) population. In addition, the significantly different items in male and female were different. These results may suggest that the mechanism of CPPD deposition may be different by gender. References: [1] Nagaosa Y, et al. Development of a logically devised line drawing atlas for grading of knee osteoarthritis. Ann Rheum Dis. 2000;59:587–95. [2] Zhang W, et al. European League Against Rheumatism recommendations for calcium pyrophosphate deposition. Part I: terminology and diagnosis. Ann Rheum Dis. 2011;70:563–70. [3] Ryu K, et al. The prevalence of and factors related to calcium pyrophosphate dehydrate crystal deposition in the knee joint. Osteoarthritis Cartilage. 2014;22:975–9. Disclosure of Interest: None declared